2009
DOI: 10.1136/jmg.2008.058958
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of de novo mutations in Li-Fraumeni syndrome

Abstract: The possibility that de novo germline TP53 mutations are relatively common has implications for testing and the identification of potential Li-Fraumeni syndrome in patients with little or no family history of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 19 publications
2
94
0
7
Order By: Relevance
“…Some of the CPC patients with p53 germline mutations do not have any family history of LFS [101,103,112]. Considering that CPC normally occurs early in life, prior to the occurrence of additional LFS-related cancers, it is of high importance to screen all patient with CPC for p53 germline mutations and family history of LFS [113].…”
Section: Cns Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the CPC patients with p53 germline mutations do not have any family history of LFS [101,103,112]. Considering that CPC normally occurs early in life, prior to the occurrence of additional LFS-related cancers, it is of high importance to screen all patient with CPC for p53 germline mutations and family history of LFS [113].…”
Section: Cns Tumorsmentioning
confidence: 99%
“…De novo cases have also been reported. In a report from 2009, 7-20% of the TP53 germline mutations were claimed to be de novo mutations [103].…”
Section: Li-fraumeni (Tp53) Syndrome (Lfs)mentioning
confidence: 99%
“…Clinically, the present study revealed that only one patient with double germline mutations of TP53 D49H and A159D had typical Li-Fraumeni-like syndrome, and the remaining 5 cancer patients had family histories of cancer. Considering the several reports demonstrating that 92-95% of individuals who had germline TP53 pathogenic variants met the revised Chompret criteria for germline TP53 mutation screening (5,18,21), the incidence developing typical clinical features in patients with germline TP53 D49H mutation is lower than expected. According to these information, it is possible to postulate that germline TP53 D49H mutation may have lower pathogenic activities, and that the mutation is likely to be low-penetrant.…”
mentioning
confidence: 99%
“…Most of the current evidence comes from studies in Europe and North America (15). Studies in Brazil have shown that a particular mutant, p.R337H, has incomplete penetrance and may be quite common due to a founder effect (estimated frequency in the general population: 1:300 in certain regions) (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%